Perkembangan Kepribadian Secara Spiritual dalam Perspektif Bediuzzaman Said Nursi - Zaprulkhan Zaprulkhan (Farabi, 2017)
In the perspective of humanistic psychology, personality development is implemented through self-actualization and peak experiences. Self-actualization is a form of actualizing one's passion in line with expectations and potential. While the peak experience is the culmination of the development of man himself when he has found himself at the peak of development using the entire faculty. For humanistic psychology, the whole development of the human personality rests on the willingness of a person itself and has nothing to do with religion or God. In this context, Said Nursi presents a different perspective. According to Nursi, the development of human personality have to rely on the realm of faith in God. Because faith is a sacred relationship between man and God that became the basis of his spiritual personality development. Similarly, because the human being as a comprehensive mirror that can reflect names of God, the spiritual development of the human personality can be actualized with names of God manifestation. Therefore, this article discusses the development of personality in perspective Said Nursi, which is based on the Quran and Sunnah.